Progress Report for the Uttarakhand Third Five-Year Plan 1962-63 - Planning Commission (Planning Commission, 1963)
Expansion of Multi-purpose Horticulture Farms—All the eleven existing Multi-purpose Horticulture Farms functioned effectively. The new farm at Kothiyalsain in district Chamoli could not be started as the local people could not be persuaded to transfer the land by negotiation on reasonable terms. The local demand to acquire the requisite land is being examined. Farms and nurseries at Pithoragarh maintained 4,337 mother plants of various fruits and produced 1,40,278 fruit and nut plants during the year. The number of plants budded and grafted d u ring the year stood at 9,872. Besides, about 133 Km, of honey was also produced at Balanti and Sirkha-Bhatka farms. In Chamoli the Subhain Farm being situated at the height of about 10,500 ft. from sea level remained completely covered with snow during the last quarter. In Uttarkashi the Raithal-Harsil and Jarmola farms are now producing fruit plants in sufficient quantity. As many as 7,558 surplus plants were supplied to the adjoining districts of Tehri and Pauri. Besides, 2.15 acres were reclaimed in the Raithal and Jarmola farms and 1,67,382 seedlings were planted for further production. In the context of the changed circumstances in the Border area special emphasis is being laid on the production of vegetables and for this purpose 8,000 ft. length of Irrigation channel has been constructed to bring v. ater in the Raithal Farm.
Progress Report
Government of Uttarakhand